Public Support for Policies to Reduce Risk After Hurricane Sandy. Issue 6 (7th April 2014) - Greenberg, Michael R.; Weiner, Marc D.; Noland, Robert; Herb, Jeanne; Kaplan, Marjorie; Broccoli, Anthony J.
<x xml:space="preserve">Abstract</x> A phone survey was conducted in New Jersey in 2013 four months after the second of two major devastating tropical storms (Sandy in 2012 and Irene in 2011). The objective was to estimate public support for restricting land uses in flood zones, requiring housing to be built to resist storm waters, and otherwise increasing mitigation and resilience. Respondents who supported these mitigation and resilience policies disproportionately were concerned about global climate change, trusted climate scientists and the federal government, and were willing to contribute to a redevelopment program through taxes, bonds, and fees. They also tended to have collectivist and egalitarian worldviews. Half of the respondents supported at least four of the seven risk‐reducing policies. How their support translates into public policy remains to be seen. Lack of willingness to personally fund these policies is an obstacle.